How the Pigeonhole Principle Can be Applied to Verify the Number of Classrooms Needed - Rozi, Syamsyida; Yurinanda, Sherli; Sarmada, Sarmada; Afrianda, Vionica; Sormin, Corry (ZERO: Jurnal Sains, Matematika dan Terapan, 2024)
Classrooms are one of the main needs for educational institutions to carry out learning activities and are an important element in creating an optimal learning environment for educators and students. Determining the number of classrooms should be done through the thorough calculation. The aim of this research is to perform how pigeonhole principle can be applied to verify the numbers of classroom needed. In working with pigeonhole principle, it should be clear what will be “pigeon”, and what will be “pigeonhole”. According to the results of this research, as we took the case study for Faculty of Science and Technology Universitas Jambi which currently build a new building, if FST wants to allocate the rooms for each department, it will need 52 classrooms based on scheme 1 and 58 classrooms based on scheme 2. While if FST does not consider the allocation for each department, then it will need 45 rooms based on scheme 1 and 46 classrooms based on sheme 2.